THE INFLUENCE OF MEDIA ON THE PROMOTION OF SCHOOL FINANCING MANAGEMENT BASED ON SOCIAL CAPITAL EMPOWERMENT - Fuadah, Yayu Tsamrotul; Izzah, Azqiya Akidatul; Murtafiah, Nurul Hidayati (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
The limited source of education funding in Indonesia is an issue that never stops rolling. Managing school funding sources does not only involve financial, material, and school personnel capital but also related to managing social capital. The selection of social capital as an alternative to madrasah empowerment needs to begin with the formation of critical awareness by each madrasa, that change is a necessity that needs to be done to free madrasahs from helplessness.Â  Social capital is just one of the other capitals that supports education funding at the macro and micro levels. The application of social capital supported by trust, social norms and social networks in financing education in schools is expected to increase cooperation in order to achieve the common goal of building independent human beings.Â